Posisi Filsafat di Antara Sains, Seni, dan Agama: Kajian Integratif dalam Perspektif Filsafat Islam Modern - Songyanan, Afifudin; Anwar, Hamdani (Lembaga Intelektual Muda (LIM) Maluku, 2026)
This study aims to analyse the position of philosophy in relation to science, art, and religion from an Islamic perspective. The study uses a qualitative-philosophical approach with a literature review method of classical and contemporary sources discussing Islamic philosophy, epistemology, and the integration of science. The data is analysed through reflective and comparative reasoning to identify the role of philosophy in building interdisciplinary relationships. The results show that philosophy functions as an epistemological framework that bridges reason and revelation in religion, provides an ontological basis for the development of science, and serves as a conceptual foundation for aesthetic expression in art. From an Islamic perspective, philosophy, science, art, and religion are not in conflict with one another, but rather complement each other within the framework of tawhid, which affirms the unity of knowledge, beauty, and faith.